2022
DOI: 10.3390/plants11050677
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Gene Regulatory Network of Maize Hybrid ZD309 under Heat Stress by Transcriptomic and Metabolomic Analysis

Abstract: Maize is an important cereal crop but is sensitive to heat stress, which significantly restricts its grain yield. To explore the molecular mechanism of maize heat tolerance, a heat-tolerant hybrid ZD309 and its parental lines (H39_1 and M189) were subjected to heat stress, followed by transcriptomic and metabolomic analyses. After six-day-heat treatment, the growth of ZD309 and its parental lines were suppressed, showing dwarf stature and rolled leaf compared with the control plants. ZD309 exhibited vigorous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Similarly, it has also been reported that DEGs in garlic are mainly distributed in the phenylpropanoid biosynthesis (sot00940) and plant hormone signal transduction (sot04075), which is related to both long and short daylight treatment ( Atif et al, 2021 ). The results in this study coincided with Liu et al (2022) who demonstrated that under the heat stress of maize for KEGG analysis, DEGs were mainly enriched in plant hormone signal transduction, alanine, aspartate, and glutamate metabolism, ABC transporter, and zeatin biosynthesis.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, it has also been reported that DEGs in garlic are mainly distributed in the phenylpropanoid biosynthesis (sot00940) and plant hormone signal transduction (sot04075), which is related to both long and short daylight treatment ( Atif et al, 2021 ). The results in this study coincided with Liu et al (2022) who demonstrated that under the heat stress of maize for KEGG analysis, DEGs were mainly enriched in plant hormone signal transduction, alanine, aspartate, and glutamate metabolism, ABC transporter, and zeatin biosynthesis.…”
Section: Discussionsupporting
confidence: 90%
“…The photosynthetic machinery takes the brunt of the damage caused by HTS, making the photosynthetic system highly sensitive to HTS [57]. HTS primarily affects photosynthesis and the expression of photosynthesis-related genes by increasing the generation of ROS, destroying photosystem II [40,58]. In this work, HTS induced the downregulation of photosynthesis-related genes in both varieties (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Under the threat of climate change, improving the heat tolerance of maize is a particularly important goal in maize breeding. Studies have consistently shown that HTS is significantly damaging to the health, growth, and biomass accumulation of maize [39,40]. Maize subjected to HTS, both MDA and ROS are overproduced and accumulate in organelles, thereby causing oxidative damage [5].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were aspirated and added to new 96‐well plates after centrifugation at 4000 × g for 20 min. The samples were kept at −80°C until they were analyzed using liquid chromatography‐mass spectrometry (LC–MS) (Liu et al, 2022). Furthermore, pooled quality control (QC) samples were also prepared by combining 10 μl of each extraction mixture (LC‐BIO Technologies Co. Ltd.).…”
Section: Methodsmentioning
confidence: 99%